1977
DOI: 10.1002/kin.550090512
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effects in the gas‐phase eliminations of alpha;‐substituted alkyl chlorides the pyrolyses of 2‐chloro‐3‐methylbutane and pinacolyl chloride

Abstract: The gas-phase pyrolyses of 2-chloro-3-methylbutane and pinacolyl chloride in the temperature range of 345390°C and pressure range of 6@220 mm Hg are homogeneous and unimoleeular in a seasoned reaction vessel. The temperature dependence of the rate constants is given by the Arrhenius equations log kl (sec-l) = (13.80 f 0.24) -(49,700 f 700) cal/mo1/2.303RT log k, (sec-') = (12.99 f 0.09) -(47,200 I ! = 250) cal/mo1/2.303RT and respectively. The Wagner-Meerwein rearrangement was not observed in these elimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Calculations for CH 3 /F interchange in neopentyl fluoride gave a threshold energy of 87.2 kcal mol −1 , and the interchange reaction of methyl or other groups with a fluorine atom will have very high activation energies and interchange will not be important. Chuchani and co-workers have suggested that the small (10%) yield of 2,3-dimethyl-1-butene and 2,3-dimethyl-2-butene from pyrolysis of 2-chloro-3,3-dimethylbutane (pinacolyl chloride) arises from a Wagner−Meerwein rearrangement. However, a CH 3 /Cl interchange mechanism would be preferred by analogy to neopentyl chloride.…”
Section: Discussionmentioning
confidence: 99%
“…Calculations for CH 3 /F interchange in neopentyl fluoride gave a threshold energy of 87.2 kcal mol −1 , and the interchange reaction of methyl or other groups with a fluorine atom will have very high activation energies and interchange will not be important. Chuchani and co-workers have suggested that the small (10%) yield of 2,3-dimethyl-1-butene and 2,3-dimethyl-2-butene from pyrolysis of 2-chloro-3,3-dimethylbutane (pinacolyl chloride) arises from a Wagner−Meerwein rearrangement. However, a CH 3 /Cl interchange mechanism would be preferred by analogy to neopentyl chloride.…”
Section: Discussionmentioning
confidence: 99%
“…of decomposition of 2-chloro-2-methylbutane (1) and of 2-chloro-2,3-dimethylbutane (2) indicates that for long reaction times the final pressure Pf should be twice the initial pressure P0. The average experimental results of…”
Section: Resultsmentioning
confidence: 99%